aRTist Handbook - Bellon, Carsten; Binder, Felix; Plotzki, David (2021)
This manual is intended as a practical guide for the use of the radiographic simulator aRTist, a software package for computer simulation of radiographic testing developed by Bundesanstalt für Materialforschung und -prüfung (BAM), Berlin, German
Keywords: aRTist; Simulation; Handbook